2021
DOI: 10.2147/dddt.s307478
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Sufentanil Decreased the EC50 of Epidural Ropivacaine for Labor Analgesia in Healthy Term Pregnancy

Abstract: Objective: The optimal concentration of ropivacaine as epidural labor analgesia combined with sufentanil has not been established. This study aimed to determine the median effective concentration (EC50) of epidural ropivacaine for labor analgesia in healthy term pregnancy when co-administered with sufentanil as an adjuvant or alone. Patients and Methods: Sixty healthy parturients scheduled for epidural labor analgesia were enrolled in the study. They were divided into a saline group (Group C) and an epidural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In this study, ropivacaine was used as a local anesthetic, mainly on the basis of ropivacaine's advantages of sensory and motor nerve separation and less influence on postoperative movement, and compared with other local anesthetics, ropivacaine also has advantages of low cardiac and central toxicity and long acting time [20]. A series of studies have shown that its analgesic effect in ophthalmic surgery, dental surgery, and obstetrical and gynecological surgery is superior to that of other anesthetic drugs [21][22][23][24]. Ketorolac is a nonsteroidal anti-inflammatory and analgesic drug that can exert analgesic effects by inhibiting the production of inflammatory pain-causing transmitters.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ropivacaine was used as a local anesthetic, mainly on the basis of ropivacaine's advantages of sensory and motor nerve separation and less influence on postoperative movement, and compared with other local anesthetics, ropivacaine also has advantages of low cardiac and central toxicity and long acting time [20]. A series of studies have shown that its analgesic effect in ophthalmic surgery, dental surgery, and obstetrical and gynecological surgery is superior to that of other anesthetic drugs [21][22][23][24]. Ketorolac is a nonsteroidal anti-inflammatory and analgesic drug that can exert analgesic effects by inhibiting the production of inflammatory pain-causing transmitters.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the process of clinical practice, it is found that many pregnant women have severe labor pain before entering the active stage. During the latent period of labor, fentanyl was injected into the epidural space of parturients, and the study indicated that there exhibited no difference in labor time and delivery outcome between labor analgesia and active labor analgesia [ 17 ]. Under the premise of ensuring medical safety, we pursue medical comfort and humanization.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction. After consulting the literature and expert discussion, we designed patients' follow-up satisfaction, a total of 10 items, and recorded patients' satisfaction with follow-up management mode, health education, medical and nursing service, appointment registration process [17]. It is assigned into four dimensions: very satisfied, satisfied, general, and dissatisfied.…”
Section: Observation Indicatormentioning
confidence: 99%
“…Imperative labor analgesia can reduce pain and exert a critical action in ensuring the safety of mother and baby. Due to its stable hemodynamics and strong analgesic effect, SUF is broadly adopted in epidural labor and analgesic delivery [ 20 ]. Multiple reports have elucidated that SUF pretreatment and post-treatment have protective effects on PE parturients.…”
Section: Discussionmentioning
confidence: 99%